EVALUATION OF ANTIMICROBIAL POTENTIALITY OF 50 PERCENT AQUEOUS ETHANOLIC LEAF EXTRACT OF Acacia nilotica Willd. - DAS, NEELA; CHATTERJEE, PADMA (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objectives: To study the antimicrobial property of 50percent aqueous ethanolic leaf extract of Acacia nilotica (L.) Willd. against few micro organisms. Method: The leaves of Acacia nilotica (L.) Willd. were sequentially soaked in petroleum Â ether (60-800 C), chloroform, benzene and 50percent aqueous ethanol, extracts were collected, filtered and concentrated. Antimicrobial potentiality of the extracts were tested against few micro-organisms. Result: Acacia nilotica (L.) Willd. exhibited antifungal effect against Rhizoctonia solani. Conclusion: The plant leaf extract can be used as antimicrobial agent against Rhizoctonia solani Key words: phytochemical products, antimicrobial property, bioassay.